DETEKSI HELM KESELAMATAN KERJA BARBASIS ANDROID MENGGUNAKAN METODE PCA (Component Principal Analys) - Firdiyan Syah; Hasti Hasanati (Jurnal Dinamika Informatika, 2021)
The development of face detection can be utilized in various fields, one of which is to detect work safety tools such as protective helmets in a project that requires work security. The face area is a part of the human body that is the focus of attention because it is the basis for detection because the face plays an important role by showing identity and emotion. Detecting work safety equipment in the form of a helmet is a challenge because of how to know the difference between a face and a helmet and not. Therefore, the face is used as an organ of the human body which is used as an indication for detection and can even be developed into a person's recognition or face recognition. Face recognition technology is a method used for detecting the discovery of images and videos. This research is to create a design concept to detect the face area using an android-based safety helmet. In this system, the pca method is used. Pca method is used for feature extraction from training and test images. This study aims to detect faces using a helmet properly with the hope that the accuracy of this method reaches 90%..